Risk Factors Associated With Hospitalization and Death in COVID-19 Breakthrough Infections - Suleyman, Geehan; Fadel, Raef; Brar, Indira; Kassab, Rita; Khansa, Rafa; Sturla, Nicholas; Alsaadi, Ayman; Latack, Katie; Miller, Joseph; Tibbetts, Robert; Samuel, Linoj; Alangaden, George; et al. (Open forum infectious diseases, 2022)
Abstract Background Characterizations of coronavirus disease 2019 (COVID-19) vaccine breakthrough infections are limited. We aim to characterize breakthrough infections and identify risk factors associated with outcomes. Methods This was a retrospective case series of consecutive fully vaccinated patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a multicenter academic center in Southeast Michigan, between December 30, 2020, and September 15, 2021. Results A total of 982 patients were identified; the mean age was 57.9 years, 565 (59%) were female, 774 (79%) were White, and 255 (26%) were health care workers (HCWs). The median number of comorbidities was 2; 225 (23%) were immunocompromised. BNT162b2 was administered to 737 (75%) individuals. The mean time to SARS-CoV-2 detection was 135 days. The majority were asymptomatic or exhibited mild to moderate disease, 154 (16%) required hospitalization, 127 (13%) had severeâ"critical illness, and 19 (2%) died. Age (odds ratio [OR], 1.14; 95% CI, 1.04â"1.07; Pâ...<â...001), cardiovascular disease (OR, 3.02; 95% CI, 1.55â"5.89; Pâ...=â...001), and immunocompromised status (OR, 2.57; 95% CI, 1.70â"3.90; Pâ...<â...001) were independent risk factors for hospitalization. Additionally, age (OR, 1.06; 95% CI, 1.02â"1.11; Pâ...=â...006) was significantly associated with mortality. HCWs (OR, 0.15; 95% CI, 0.05â"0.50; Pâ...=â...002) were less likely to be hospitalized, and prior receipt of BNT162b2 was associated with lower odds of hospitalization (OR, 0.436; 95% CI, 0.303â"0.626; Pâ...<â...001) and/or death (OR, 0.360; 95% CI, 0.145â"0.898; Pâ...=â...029). Conclusions COVID-19 vaccines remain effective at attenuating disease severity. However, patients with breakthrough infections necessitating hospitalization may benefit from early treatment modalities and COVID-19-mitigating strategies, especially in areas with substantial or high transmission rates.